2006
DOI: 10.1055/s-2006-931622
|View full text |Cite
|
Sign up to set email alerts
|

Transzygomatic-Subtemporal Approach for Middle Meningeal-to-P2 Segment of the Posterior Cerebral Artery Bypass: An Anatomical and Technical Study

Abstract: We evaluated the use of a bypass between the middle meningeal artery (MMA) and P2 segment of the posterior cerebral artery (PCA) as an alternative to an external carotid artery (ECA-to-PCA) anastomosis. Five adult cadaveric heads (10 sides) were used. After a temporal craniotomy and zygomatic arch osteotomy were performed, the dura of the floor of the middle cranial fossa was separated and elevated. The MMA was dissected away from the dura until the foramen spinosum was reached. Intradurally, the carotid and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
11
0
3
Order By: Relevance
“…However, Ustun et al 22 and Terasaka et al 19 both proposed dissecting the masseter muscle first and then sectioning and removing the zygomatic arch.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ustun et al 22 and Terasaka et al 19 both proposed dissecting the masseter muscle first and then sectioning and removing the zygomatic arch.…”
Section: Discussionmentioning
confidence: 99%
“…Early division of middle meningeal artery before passing through FS may be the cause of duplication of foramen spinosum [6,7,8]. Foramen spinosum has been described as an important landmark for microsurgical procedure involving middle cranial fossa particularly when using middle meningeal artery as a donor graft for either internal carotid artery or posterior cerebral artery bypass surgery [9,10]. Hence detailed anatomical knowledge including developmental aspect is really worthwhile as far as neurosurgery and radiology is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…The latter of the aforementioned procedures notes that the MMA trunk must be transected immediately before the bifurcation of its anterior and posterior branch at the location inside the dura and over the FS [16]. The MMA typically bifurcates intracranially; however, in the case presented herein, both the left and right MMA bifurcated extracranially.…”
Section: Discussionmentioning
confidence: 96%
“…Ustun et al [15] performed an anatomical study through which the spinosum was exposed extradurally in the bypass of the middle meningeal artery (MMA) with the petrous internal carotid artery (ICA) for the treatment of high cervical vascular lesions or tumors occupying the high ICA. Ustun et al [16] also reported an alternative to the anastomosis of the external carotid artery to the posterior cerebral artery (ECA-to-PCA) for the treatment of central vertigo and dizziness, commonly caused by vertebrobasilar insufficiency, by creating a bypass between the MMA and P2 segment of the PCA.…”
Section: Discussionmentioning
confidence: 99%